All-in-one 3D acceleration sensor based on coded liquid–metal triboelectric nanogenerator for vehicle restraint system. (March 2021) - Zhang, Binbin; Wu, Zhiyi; Lin, Zhiming; Guo, Hengyu; Chun, Fengjun; Yang, Weiqing; Wang, Zhong Lin
Graphical abstract: Abstract: Vehicle restraint systems play an irreplaceable role to limit passenger injuries when an accident occurs, in which, the 3D acceleration sensor (AS) is an essential component to detect the collision position and force. However, there are some defects for commercial sensors such as passive sensing, low sensitivity and high manufacturing cost. Here, we report a lightweight, high-sensitivity, low-cost and self-powered 3D AS based on a liquid–metal triboelectric nanogenerator (LM-TENG). In view of the coded strategy of the electrodes, the 3D AS retains the smallest size, lowest weight and highest integration compared to the currently reported self-powered AS. The fabricated sensor possesses wide detection range from 0 to 100 m/s 2 in the horizontal direction and 0 to 50 m/s 2 in the vertical direction at a sensitivity of 800 mV/g. The open-circuit voltage shows a negligible decrease after continuously operating for 100, 000 times, showing excellent stability and durability. Furthermore, the 3D AS is demonstrated as a part of the airbag system to spot the collision position and force of the car simultaneously. This work will further promote the commercialization of TENG-based sensor and exhibits a prospective application in the vehicle restraint system.